2012
DOI: 10.1097/aln.0b013e31824be8c7
|View full text |Cite
|
Sign up to set email alerts
|

Tau Phosphorylation and Sevoflurane Anesthesia

Abstract: Background: There is a growing interest in the involvement of anesthetic agents in the etiology of postoperative cognitive dysfunction. Recent animal studies suggest that acute anes-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
89
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(96 citation statements)
references
References 59 publications
5
89
1
1
Order By: Relevance
“…Moreover, while the multiple exposures of sevoflurane from P6 to P8 still induced Tau phosphorylation at P10 (Figure 2C and 2D), the single exposure of sevoflurane anesthesia at P6 did not induce Tau phosphorylation at P6 (Figure 2A and 2B). These findings suggested that the Tau phosphorylation resulted from multiple exposures of sevoflurane but not a single exposure of sevoflurane, which were consistent with the results from the studies by Shen et al 9 and Le Freche et al 45 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, while the multiple exposures of sevoflurane from P6 to P8 still induced Tau phosphorylation at P10 (Figure 2C and 2D), the single exposure of sevoflurane anesthesia at P6 did not induce Tau phosphorylation at P6 (Figure 2A and 2B). These findings suggested that the Tau phosphorylation resulted from multiple exposures of sevoflurane but not a single exposure of sevoflurane, which were consistent with the results from the studies by Shen et al 9 and Le Freche et al 45 .…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, repeated exposures (once every month for five months) of sevoflurane in 5 to 6 month-old mice induced Tau phosphorylation and cognitive impairment in the mice 45 . However, the effects of the sevoflurane anesthesia (e.g., 3% sevoflurane two hours daily for three days) on Tau phosphorylation in young mice have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the pharmacological drugs effect on proteolysis pathways, given that pI and MW identification of the truncated forms may provide the cleavage site according to the antibody's epitope 34 . Interestingly, recent data have elucidated using mini-2DE the association of lifestyle and drug treatments with cognitive impairments in mouse models, as well as the biochemical profile of a new Tau mutation [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…боты синапсов, сопровождаясь снижением когнитивных функций [9,10,11]. Токсичность тау-протеина связана с ацетилированием двух лизинов (K274 и K281), кото-рые блокируют долговременные потенциалы в синапсах гиппокампа и приводят к нарушению памяти [12].…”
unclassified